Construction Overhead Cost of Tall Buildings in Bangkok Area - เทพจันทร วรวรรณ; ตั้งปกาศิต จตุพล; รู้แทนคุณ รัฐวุฒิ (Frontiers in Engineering Innovation Research, 2010)
Overhead cost is an important cost of total construction project cost. Appropriate control of overhead cost will avoid budget overrun problem. The objective of this research is to study the estimation method of construction project overhead cost in construction projects. The questionnaire survey was conducted on main contractors of tall buildings in Bangkok area. Overhead cost is categorized into 14 groups. The result reveals the ability level of cost control based on information from expert interview compared with actual overhead cost from construction project in the past.